Deep crypt secretory cells shape region-specific mucin glycosylation patterns in the mouse colon - Daisuke Sugahara; Hayato Kawakami; Yoshihiro Akimoto (PLoS ONE, 2025)
The colonic mucin layer, comprising highly glycosylated mucin proteins, is crucial for maintaining colonic health. Its region-specific glycosylation patterns are indispensable for adapting to distinct physiological and microbial environments along the colon, thus ensuring appropriate mucin layer function. However, the mechanisms underlying this region-specific glycosylation remain unknown. Here, using fluorescence-based immunohistological analyses of the colon from experimental mice, we demonstrated that along with contribution of goblet cells, as conventionally believed, mucin glycosylation involves deep crypt secretory (DCS) cells, a specialized mucin-producing cell population in the colon. Based on cKit/CD117 as a DCS cell marker, DCS and goblet cells are inversely distributed along the mouse colon: DCS cells predominate proximally, constituting nearly 70% of mucin-producing cells, whereas goblet cells are more abundant distally, indicating a dynamic shift in the predominant mucin-producing cell population along the colon. Immunofluorescence staining revealed that DCS cells produce distinctive mucin-glycans, including those with the Core3-glycan motif that exhibit region-specific distributions in the mucin layer. We found that the gradient distribution of DCS cells predominantly shapes their region-specific distribution, whereas the inverse distribution of goblet cells corresponds to the distal distribution of sulfated and sialylated glycans. Furthermore, the in situ Proximity Ligation Assay for specifically detecting Muc2 with distinct glycosylation, revealed that DCS and goblet cells produce different types of α1,2-fucosylated glycans on Muc2, indicating that the shift in the predominant mucin-producing cells drives region-specific α1,2-fucosylation on Muc2 across colonic regions. Although DCS cells are implicated in supporting the stem cell niche, their involvement in mucin production was unclear. We highlight the critical role of DCS cells in establishing regional glycosylation patterns. Our findings provide new insights into the cellular basis of mucin glycosylation, as well as their potential impact on colonic health and disease susceptibility in specific colonic regions.